2017
DOI: 10.1089/omi.2017.0044
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin GN-Glycans as Potential Postgenomic Biomarkers for Hypertension in the Kazakh Population

Abstract: Next-generation (postgenomic) biomarkers from the nascent field of glycomics now offer fresh vistas for innovation in chronic disease biomarkers and system diagnostics in clinical medicine. Our previous work has shown an association between hypertension and immunoglobulin G (IgG) glycome composition, suggesting that individual variation in N-glycosylation of IgG might contribute to hypertension pathogenesis. The present study examined, for the first time to the best of our knowledge, the IgG N-glycans as poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 44 publications
4
21
0
Order By: Relevance
“…Glycome reflects the real-time status of these intricate interplays and promises potential biomarkers for multifactorial diseases. Consistent with previous studies on IgG N-glycome and total N-glycome (Gao et al, 2017;Ge et al, 2018;Lemmers et al, 2017;Liu et al, 2018a;Lu et al, 2011;Russell et al, 2017Russell et al, , 2018bWang et al, 2016b;Yu et al, 2016), in this study, the IgG N-glycan traits were identified as significantly associated with age, sex, BMI, blood pressure, blood lipids, FBG, and HbA1c.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Glycome reflects the real-time status of these intricate interplays and promises potential biomarkers for multifactorial diseases. Consistent with previous studies on IgG N-glycome and total N-glycome (Gao et al, 2017;Ge et al, 2018;Lemmers et al, 2017;Liu et al, 2018a;Lu et al, 2011;Russell et al, 2017Russell et al, , 2018bWang et al, 2016b;Yu et al, 2016), in this study, the IgG N-glycan traits were identified as significantly associated with age, sex, BMI, blood pressure, blood lipids, FBG, and HbA1c.…”
Section: Discussionsupporting
confidence: 92%
“…Similar conclusions were also reached in studies of IgG Nglycome on chronological aging in different populations Yu et al, 2016) and hypertension in different nations from one population (Gao et al, 2017;Wang et al, 2016b). The inconsistency of significantly different glycans seen between our results and those of previous studies shows the diversity of T2DM among populations in glycome level.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous glycomics research has shown that IgG Nglycans are associated with the cardiometabolic risk factors, including hypertension (Gao et al, 2017;Liu et al, 2018c;Wang et al, 2016b), T2DM (Ge et al, 2018;Lemmers et al, 2017), central obesity (Russell et al, 2018), and dyslipidemia (Liu et al, 2018a). In this study, we described the association of IgG N-glycans with the 15 cardiometabolic risk factors in a Chinese Han population.…”
Section: Discussionmentioning
confidence: 81%
“…N-glycans attach to the conserved asparagine 297 of both heavy chains in the fragment crystallizable region of IgG and act as a switch between proinflammatory and anti-inflammatory responses of IgG (Gornik et al, 2012;Jefferis, 2009). Changes to the IgG Nglycan profiles are involved in several inflammatory diseases, such as hypertension (Gao et al, 2017;Liu et al, 2018c;Wang et al, 2016b), stroke (Liu et al, 2018b), T2DM (Ge et al, 2018;Lemmers et al, 2017), Parkinson's disease , and rheumatoid arthritis (Sebastian et al, 2016).…”
Section: Introductionmentioning
confidence: 99%